(untitled) (International Journal of Engineering and Computer Science, 2013)
Over the time developers have been trying to develop an Automated System which generates all required codes automatically. Many projects have attempted to achieve a concept called the Zero Code which is almost impossible.Tremplin is software which generates partial code automatically based on developers input for projects involving data entry screens. This software saves considerable amount of time spent for the developing code, testing and maintaining uniformity. Hence it is rightly described as Save Time in Every Project. Tremplin can auto generate code for data entry screen containing New, Save, Delete, Import Export and Search functionalities. Developing applications in Tremplin is simple. It does not require any special skills and only skill that is expected as a user is database design and SQL writing Skills.